(3GdVhGHW GdLfGFjI dMQjI GdQCi (B: s (3OQGSI ebGQfI (B/ s - (3YHOGdQMef eMeO eUWai gjcds; (3CMeO YhV HdGd s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3GTJedJ gPg GdOQGSI Ydj HjGf GdVhGHW GdLfGFjI dMQjI(B. (3h JfGhd GdJYQja HMQjI GdQCi h gh eWdb ddEfSGf ai GYJbGO eG jTGA h NGQL fWGb GdJLQje(B: (3HjfeG MQjI GdEaUGM h GdJYHjQ Yf gPG GdQCi adGHO Cf Jchf ef NdGd hSGFd GdYdGfjI GdeHjfI HGdeGOI (B171(3ef bGfhf GdYbhHGJ GdeUQi h GdeGOI (B23(3ef bGfhf GdUMGaI GdaQfSi h gi efGW GdJLQje(B: (3h HjfJ LhGR JbjjOgG MaGXkG Ydi GdMbhb h GdMQjGJ GdLOjQI HGdMeGjI GdLfGFjI(B: (3cMb GdfGS ai GdSeYI h GdTQa(B: (3h YOe gJc SJQ CSQGQ MjGJge GdNGUI(B. (3h HjfJ Cf GdCQcGf GdeTJQcI dLQGFe GdQCi gi Qcf GdYdGfjI h GdQcf GdeGOi h GdQcf GdeYfhi(B: (3CeG GdeSFhdjI GdLfGFjI agi ddeDda h QFjS GdJMQjQ h GdfGTQ h GdWGHY h GdeSJhQO h GdHGFY h GdedUb h eGdc GdLQjOI h GdTNU GdeYfhi(B: (3h GdeTQY GdaQfSi fXe GdeSFhdjI GdLfGFjI Yf gPg GdLQGFe HbGfhf eSJbd(B: (3ai Mjf Cf GdeTQY GdeUQi JQc Pdc ddbhGYO GdYGeI ddeSFhdjI GdLfGFjI(B: (3ceG Cf CSHGH GdEHGMI JfMUQ ai Mb fTQ GdCNHGQ h GdfbO h GdWYf ai CYeGd Phi GdUaI GdYehejI(B. (3h GfJgjJ Edi Cf GdeTQY GdeUQi bjO MQjI GdQCi VO Gdfjd ef bOQ h GYJHGQ GdEfSGf(B: (3h NdUJ Edj Cf GdfXGe GdeUQi jTJQW dSbhW GdMb ai JMQjc GdOYhi GdLfGFjI GdYde HGdLQjeI h HeQJcHgG(B: (3NdGakG ddfXGe GdaQfSi GdPi jTJQW GdYde HhbhY GdLQjeI abW(B: (3h bO GdZi GdMHS GdGMJjGWi YbH UOhQ GdbQGQ HbGfhf Qbe (B58 (3dSfI (B2012: (3h OddJ Ydi Cf GNJUGU eMGce GdLfGjGJ HfXQ LfM GdQCi h GdJYHjQ jNd HeHGOF GdJbGVi Ydi OQLJjf h GdeSGhGI h Mb GddLhA Edi GdbGVi GdWHjYi(B: (3h CNjQkG HjfJ LhGR GNJUGU GdeMGce GdYScQjI h eMGce Cef GdOhdI HfXQ LQGFe GdQCi h GdJYHjQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2016s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B251-264s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdVhGHW GdLfGFjIs; (3GdYdGfjIs; (3GdbUO GdLfGFis; (3MQjI GdQCjs; (3JLQje GdGgGfI GdYdfjIs; (3LQjeI GdbPa GdYdfjs; (3MQeI GdMjGI GdNGUIs; (3GdeMGce GdYScQjI heMGce Gef GdOhdIs; (3GdMb aj fTQ GdGNHGQs; (3MGdI GdHK GdeHGTQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs